2016
DOI: 10.1371/journal.pone.0147019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of South African Ovine Herpesvirus 2 Strains Based on Selected Glycoprotein and Tegument Genes

Abstract: Ovine herpesvirus 2 (OvHV-2), is the causative agent of sheep-associated malignant catarrhal fever (SA-MCF), a generally fatal disease of cattle and other captive wild ruminants. Information on the OvHV-2 strains circulating in South Africa (SA) and other African countries with regard to genetic structure and diversity, and pattern of distribution is not available. This study aimed to characterize the OvHV-2 strains circulating in SA using selected genes encoding glycoproteins and tegument proteins. To establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Four partial ORF27 coding sequences of 832 bp (missing 50 nucleotides at the 5′ end) were obtained from the PCR-positive samples. No sequence data were obtained with any of the other primer pairs described by Doboro et al [ 14 ]. All 4 ORF27 sequences were identical and distinct from the sequence of the OvHV-2 sample D35/07 used as a positive control for the PCR.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four partial ORF27 coding sequences of 832 bp (missing 50 nucleotides at the 5′ end) were obtained from the PCR-positive samples. No sequence data were obtained with any of the other primer pairs described by Doboro et al [ 14 ]. All 4 ORF27 sequences were identical and distinct from the sequence of the OvHV-2 sample D35/07 used as a positive control for the PCR.…”
Section: Resultsmentioning
confidence: 99%
“…The OvHV-2 sequences were downloaded, aligned, and trimmed to match the Egyptian sequences. The ORF27 sequence data published by Doboro et al [ 14 ] (5 identical sequences) were extracted from the article and added manually. A maximum-likelihood phylogenetic tree of the 20 ORF27 nucleotide sequences included in this study is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations